2014
DOI: 10.1007/s12070-014-0786-3
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Higher Origin of Facial Artery and its Surgical Significance

Abstract: Facial artery plays a key role in blood supply of the face. Facial artery one of the anterior branches of the external carotid artery originates within the carotid triangle. Variation in the origin of the facial artery was observed on two sides out of 60 sides in 30 cadavers. Facial artery was observed originating at the level just below the maxillary artery within the parotid gland. Facial artery may originate as linguo-facial trunk or thyro-linguo-facial trunk. Other developmental variations have also been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Many authors noted variations in origin, such as the facial artery originating with the lingual artery from a common trunk viz. the linguofacial trunk (Ozgur et al, 2008;Troupis et al), and an intraparotid origin (Mangalgiri et al, 2015). Although the current study did not find any intraparotid origins, it did observe origins from the linguofacial trunk ( Fig.…”
Section: Origincontrasting
confidence: 43%
See 1 more Smart Citation
“…Many authors noted variations in origin, such as the facial artery originating with the lingual artery from a common trunk viz. the linguofacial trunk (Ozgur et al, 2008;Troupis et al), and an intraparotid origin (Mangalgiri et al, 2015). Although the current study did not find any intraparotid origins, it did observe origins from the linguofacial trunk ( Fig.…”
Section: Origincontrasting
confidence: 43%
“…Various studies have classified the facial arteries' branching pattern and termination, but few have reported on the variable origin (Troupis et al, 2015;Mangalgiri et al, 2015). In addition, few studies have reported on the differences of the facial artery anatomy between sex and laterality.…”
Section: Introductionmentioning
confidence: 99%
“…Another major artery that supplies blood to the external part of the nose is the facial artery (FA). FA stems from the external carotid artery and divides into the angular artery, bifurcating further to the lateral nasal artery and the superior labial artery [14,15]. The prevalence of veins in the nasal mucosa is favourable for effective systemic targeting.…”
Section: The Physiology Of Nasal Cavitymentioning
confidence: 99%
“…To illustrate, some studies have reported that the facial and lingual arteries have a common trunk called the linguofacial artery which arises from the external carotid. [ 8 9 ] Furthermore, this artery may originate within the parotid gland, referred to as the intra-parotid origin. [ 10 ] It has been shown that there are some variations related to the course and branches of the right facial artery compared to the left one.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] In terms of the facial artery development, it is indicated that this artery is prone to agenesis, enlargements, and excessive narrowness, all of which are related to the development of the cardiovascular system in the fetus and how the pharyngeal arches and different branches of each disappear and fuse. [ 8 13 ] In addition, this artery may not lead to the medial canthus but goes towards the zygomatic arch or infraorbital which is recognized as a deviated branch. [ 14 15 16 ] Due to the wide range of variations of this artery in the way of blood supply to the face and the number of branches separated from it, different categories are made for the variants of this artery.…”
Section: Introductionmentioning
confidence: 99%